Novel Bilateral Extracavitary Approach for Thoracolumbar Decompression. Issue 2 (5th May 2017) - Mullin, Jeffrey P; Chan, Alvin Y; Bennett, Emily; Steinmetz, Michael P
Abstract: BACKGROUND: Bilateral extracavitary approach (BECA) is an option for decompression cases that require a more extended ventral approach. The clear advantage is increased accessibility to the most ventral aspects of the spine from a bilateral perspective. OBJECTIVE: To assess the safety and efficacy of thoracic and thoracolumbar decompression and/or reconstruction from BECA. METHODS: A retrospective chart review was performed reviewing all patients who underwent BECA for thoracolumbar decompression from 2003 to 2012 at our institution. We recorded patient baseline characteristics, physical exam, surgical indications, perioperative interventions, and outcomes. RESULTS: We performed 82 lateral extracavitary approaches and 10 BECAs. BECA indications included neoplasm, infection, and kyphotic deformity. Average patient age was 58 yr; 80% of BECA patients were male. Estimated blood loss was typically 1 to 3 L. Average length of stay postoperative was 12 d. Two patients required revisions; one for infection and one for revision of misplaced hardware. Eight patients improved at least one grade on the American Spinal Injury Association Impairment Scale (ASIA) or was originally ASIA E. Two patients declined 1 to 2 ASIA grades. Average length of follow-up was 16.8 mo. CONCLUSION: BECA is an efficient technique with acceptable complication rates and similar risks to unilateral approaches. It should be considered when extensive bilateral decompression and/or reconstruction of the anterior thoracic or thoracolumbar spine is required.